Magnetostructural Characterization of Oxalamide Dihalo‐Bridged Copper Dimers: Intra‐ and Interdimer Interactions Studied by Single‐Crystal Electron Spin Resonance Spectroscopy. Issue 17 (1st August 2017) - Žilić, Dijana; Maity, Debdeep; Cetina, Mario; Molčanov, Krešimir; Džolić, Zoran; Herak, Mirta
Abstract: Detailed single‐crystal electron spin resonance (ESR) analysis of oxalamide complexes with halogen‐bridged copper dimers, supported by X‐ray, magnetic susceptibility, and powder ESR studies, is reported. Four complexes with two different ligands are synthesized: [CuL A (μ‐X)]2 and [CuL V (μ‐X)]2, for which L A = N ‐(l ‐alanine methyl ester)‐ N ′‐[(2‐pyridine‐2‐yl)methyl]oxalamide and L V = N ‐(l ‐valine methyl ester)‐ N ′‐[(2‐pyridine‐2‐yl)methyl]oxalamide, for which X=Cl or Br. X‐ray analysis shows that the geometry at each copper(II) ion is square pyramidal, whereas two pyramids share one base‐to‐apex edge with parallel basal planes. The complexes are linked by hydrogen bonds into infinite chains and are further linked into a 3D network. Susceptibility measurements show that the copper centers in the dimers are weakly antiferromagnetically coupled (| J |≈1–2 cm −1 ). From powder ESR spectroscopy, the g values and d x 2 - y 2 orbital as the ground state of the unpaired electron are determined. The complexes show unusual anisotropic splitting and merging of the ESR lines if their single crystals rotate in a magnetic field. The observation of this partially resolved intradimer dipolar splitting enables estimation of the weak interdimer exchange interaction parameter | J ′|≈0.001 cm −1 . Abstract : Single and looking : Single‐crystal electron spin resonance spectroscopy experiments reveal unusual anisotropic splitting and merging of lines if crystals of newly synthesized dihalo‐bridged oxalamide copper(II) dimers rotate in a magnetic field. The observation of this partially resolved intradimer dipolar splitting enables estimation of weak interdimer exchange interactions.